Impossible is Nothing. A Modernisation of the Polish Academy of Sciences - Dominik Antonowicz (Foresight and STI Governance)
The Polish Ministry of Science and Higher Education has recently undertaken attempts to reform the Polish Academy of Sciences. Different social actors took part in this long political and legal process. Contrary to the public debate, in which the reforms are being defined as a a component of modernization of Polish science and higher education, the author consider it as means of redistributing the balance of power in the Polish academia. It allows not only to identify changes but also to provide their better understanding. The main focus is directed to the political confrontation between the Polish academic oligarchy and the government.